Optimizing Time Calculation with Extended Working Hours in the Periodic Road Maintenance Project on Jl. Ir. Soekarno Ruas 3, Blitar City - Eka Shodiq Permadi; Hanie Teki Tjendani; Budi Witjaksana (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Road maintenance is a strategic effort to support community mobility and economic development. This study aims to determine the optimal duration and analyze the cost impacts of implementing the Time Cost Trade Off (TCTO) method. The method is applied through critical path analysis and adding overtime hours to reduce the project duration. Data is collected from project documents such as daily reports, S-curves, and cost budget plans, then analyzed using Microsoft Project software. The results show that the project duration can be shortened to 117 days with an additional cost of IDR 176,614,724.00, which is lower than the potential delay penalty of 1% per day. This adjustment leads to a time savings of 8.6% without causing significant changes to the project's organizational structure. The TCTO method proves to be a practical solution for addressing delays while maintaining a balance between time and cost.